Integrated Use of Fertilizers and Bio-Stimulant Affect the Growth and Seedling Development of Chili - Abro, Maria; Wahocho, Ahmed; Wagan, Maqsood Ali; Abbas, Tahira; Ahmad, Waqas; Anjum, Sumreen; Ali, Hube; Abro, Ali Raza; Wahocho, Safdar Ali; Abro, Narjis (Journal of Agriculture and Biology, 2025)
NPK fertilizer, in combination with bio-stimulants, is crucial in promoting the growth and development of chili. This study investigates the individual and combined effects of NPK fertilizers and a bio-stimulant (Hook) on the growth and morphological traits of chili (Capsicum annuum L.) seedlings. Seven treatments were applied, including NPK at three concentrations (1.5, 2.5, and 3.5 g/L), Hook (10 ml/L as a foliar spray), and their combinations. The foliar spray of Hook was applied 15 days after germination, while NPK was applied in two split doses, one week after germination and 20 days later. Ten seeds of the Advanta Hybrid hot pepper Shehzadi were sown per pot, and growth parameters were recorded at the five-leaf and six-leaf stages. Morphological traits such as plant height, number of leaves, plant spread, seedling girth, leaf area, seedling collar, chlorophyll content, root length, and seedling weight were evaluated. The results showed significant differences in growth parameters among the treatments. NPK at a lower concentration (1.5 g/L) promoted the tallest plants and the highest leaf production at both the five-leaf and six-leaf stages. Combined treatments of NPK and Hook, particularly 1.5 g/L NPK plus Hook (T5), displayed superior growth performance compared to individual applications, indicating a synergistic effect. Seedling girth, leaf area, and chlorophyll content were also notably enhanced with moderate NPK concentrations and combined treatments. Higher concentrations of NPK (3.5 g/L) and the sole application of Hook were less effective in promoting growth. The study concludes that moderate NPK (1.5–2.5 g/L) alone or with Hook (10 ml/L) significantly improves chili seedling growth, highlights the potential of optimized NPK and bio-stimulants for sustainable production.
Keywords: Chili seedlings; Growth; NPK Fertilizer; Hook; Morphology